Analisis Perhitungan Biaya dan Laba Usaha Menggunakan Pendekatan Full costing Pada UMKM Toko Buku Adijaya : Analysis of Cost and Profit Calculation Using the Approach Full costing at Adijaya Bookstore MSMEs - Tathia Aurellia; Elisabet Marisi Pardede; Icha Permata Sari; Moh Farel fedri; Nazwa Nur Shifa (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This research is motivated by the simplistic financial recording practices of the Adijaya Bookstore MSME, where the owner only calculates the Cost of Goods Sold (COGS) based on book purchase costs while ignoring operational expenses. Consequently, the reported profit fails to reflect the actual financial condition. This study aims to investigate the calculation of COGS and business profits using the Full costing method to provide more accurate financial information for managerial decision making. Furthermore, it aims to identify cost components that have not been systematically recorded and offer practical recommendations to enhance operational cost efficiency. Thus, the findings are expected to serve as a foundation for similar retail MSMEs in implementing a structured, data driven cost accounting system, enabling managerial decisions to be more rational, accountable, and oriented toward long term business sustainability. The approach adopted is a quantitative descriptive approach method utilizing the Full costing technique. Primary data were obtained through online interviews, while secondary data consisted of documentation of operational expenses and e-commerce sales reports for July. The findings indicate that the application of the Full costing method yields a more precise COGS value of Rp286,313,000, differing from the legacy method which only recorded Rp279,288,000. The store's real profit was adjusted to Rp62,797,000 from the initial estimate of Rp69,822,000. The implication of implementing this method provides a more accurate picture of profitability and assists management in identifying cost efficiencies, such as the recommendation to engage in bulk buying for packaging elements, which represent the largest operational cost.